Speciation rates are positively correlated with the rate of plumage color evolution in hummingbirds. (6th June 2021) - Beltrán, Diego F.; Shultz, Allison J.; Parra, Juan L.
Abstract: A fascinating pattern in nature is the uneven distribution of biodiversity among clades, some with low species richness and phenotypic variation in contrast to others with remarkable species richness and phenotypic diversity. In animals, communication signals are crucial for intra‐ and interspecific interactions and are likely an important factor in speciation. However, evidence for the association between the evolution of such signals and speciation is mixed. In hummingbirds, plumage coloration is an important communication signal, particularly for mate selection. Here, using reflectance data for 237 hummingbird species (∼66% of total diversity), we demonstrate that color evolution rates are associated with speciation rates, and that differences among feather patches are consistent with an interplay between natural and sexual selection. We found that female color evolution rates of multiple plumage elements, including the gorget, were similar to those of males. Although male color evolution in this patch was associated with speciation, female gorget color evolution was not. In other patches, the relationship between speciation and color evolution rates was pervasive between sexes. We anticipate that future studies on animal communication will likely find that evolution of signaling traits of both sexes has played a vital role in generating signal and species diversity.